2004
DOI: 10.1111/j.1463-5224.2004.04013.x
|View full text |Cite
|
Sign up to set email alerts
|

Inherited retinal dysplasia and persistent hyperplastic primary vitreous in Miniature Schnauzer dogs

Abstract: The objectives of this study were to define the clinical syndrome of retinal dysplasia and persistent primary vitreous in Miniature Schnauzer dogs and determine the etiology. We examined 106 Miniature Schnauzers using a biomicroscope and indirect ophthalmoscope. The anterior and posterior segments of affected dogs were photographed. Four enucleated eyes were examined using routine light microscopy and scanning electron microscopy. A pedigree was constructed and related dogs were test-bred to define the mode of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Fluorescein dye staining was negative Behind and attached to the lens, a triangularshaped echogenicity could be seen (white arrows) which continued as a tubular hyperechoic strand to the optic disk that could be seen as a hypoechoic region (black arrows) feature. Persistent hyaloid arteries are not accompanied by proliferative primary vitreous or posterior lens capsule plaque and cataracts, and PHPV may or may not be accompanied by patent hyaloid arteries (Grahn et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescein dye staining was negative Behind and attached to the lens, a triangularshaped echogenicity could be seen (white arrows) which continued as a tubular hyperechoic strand to the optic disk that could be seen as a hypoechoic region (black arrows) feature. Persistent hyaloid arteries are not accompanied by proliferative primary vitreous or posterior lens capsule plaque and cataracts, and PHPV may or may not be accompanied by patent hyaloid arteries (Grahn et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the condition is inherited as an autosomal recessive trait (MacMillan and Lipton 1978). Until now, this has been confirmed in, for instance, Miniature Schnauzers, where rd is accompanied by PHPV (Persistent Hyperplastic Primary Vitreous) (Grahn et al 2004). In Labrador Retrievers and Samoyeds, it has been established that OSD (oculoskeletal dysplasia) is inherited as an autosomal dominant condition with incomplete penetrance (Nelson and MacMillan 1983;Carrig et al 1988).…”
mentioning
confidence: 88%
“…In a study by O'Toole et al (1983), dysplastic lesions in English Springer Spaniels were detected in an ophthalmoscopic examination straight after birth, whereas Holle et al (1999) found that in the case of geographic retinal dysplasia, the lesions were rarely noticeable earlier than week 10 of life, which may be associated with tapetal development which can last for up to the first 6 months of life (Cook 2013). It has been noted that single or multiple retinal folds may become less visible with age (Grahn et al 2004) or may disappear completely, after which the fundus returns to normal (ACVO Genetics Committee 2014). This is most probably associated with a redevelopment of the retina (O'Toole et al 1983;Cispin et al 1999;Holle et al 1999;Grahn et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations